The pH-sensitve oxygenation of FeS: Mineral transformation and immobilization of Cr(VI). (15th April 2023) - Wang, Tao; Liu, Yuanyuan; Liu, Bin
Highlights: Aqueous and surface reactions rule FeS oxygenation at acidic and basic pH severally. γ-FeOOH replaces α-FeOOH and amarantite as the main product besides S 0 as pH rises. H + can regulate FeS transformation and further affect its ability to reduce Cr(VI). Increasing oxygenation time of FeS impedes Cr(VI) reduction and removal at pH 5.0. Pyrite from brief oxygenation of FeS improves Cr(VI) reduction and removal at pH 9.0. Abstract: Iron sulfide (FeS) has been widely used to reduce toxic Cr(VI) into Cr(III) in anoxic aquatic environments, where pH could strongly influence Cr(VI) removal. However, it remains unclear how pH regulates the fate and transformation of FeS under oxic conditions and the immobilization of Cr(VI). The results of this study showed that typical pH conditions of natural aquatic environment significantly affected the mineral transformation of FeS. Under acidic conditions, FeS was principally transformed to goethite, amarantite, and elemental sulfur with minor lepidocrocite through proton-promoted dissolution and oxidation. Instead, under basic conditions, the main products were lepidocrocite and elemental sulfur via surface-mediated oxidation. In typical acidic or basic aquatic environment, the pronounced pathway for the oxygenation of FeS solids may alter their ability to remove Cr(VI). Longer oxygenation impeded Cr(VI) removal at acidic pH, and a decreasing ability to reduce Cr(VI) caused a drop in Cr(VI) removal performance. Cr(VI) removal decreased from 733.16 to 36.82 mg g −1 with the duration of FeS oxygenation increasing to 5760 min at pH 5.0. In contrast, newly generated pyrite from brief oxygenation of FeS improved Cr(VI) reduction at basic pH, followed by a drop in Cr(VI) removal performance due to the impaired reduction capacity with increasing to the complete oxygenation. Cr(VI) removal increased from 669.58 to 804.83 mg g −1 with increasing oxygenation time to 5 min and then decreased to 26.27 mg g −1 after the full oxygenation for 5760 min at pH 9.0. These findings provide insight into the dynamic transformation of FeS in oxic aquatic environments with various pHs and the impact on Cr(VI) immobilization. Graphical abstract: Image, graphical abstract